1995
DOI: 10.3354/dao023135
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive capacity of the eastern oyster Crassostrea virginica infected with the parasite Perkinsus marinus

Abstract: ABSTRACT. We studied the influence of the protozoan parasite P e r h s u s marinus (Mackin. Owen & Collier) on reproduction in the eastern oyster Crassostrea virginica (Gmelin) from 2 sub-estuaries of central Chesapeake Bay, Maryland, in 1990 and 1991 One hypothesis was that increased levels of infection by P marinus cvould result in smaller egg size and diminished lipid reserves within individual eggs. Our results did not reveal any consistent deleterious effects of l? marinus on these gametogenic characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 10 publications
2
31
0
Order By: Relevance
“…The impacts of introduced pathogens seem to have resulted in significant, widespread, and complex changes throughout the bay. The two protistan pathogens Haplosporidium nelsoni and Perkinsus marinus, classified respectively as a probable and a possible introduction, have been a significant factor in the decline in abundance of the oyster Crassostrea virginica (e.g., Andrews 1979;Kennedy 1996;see Lauckner 1983;Sindermann 1990). In Chesapeake Bay, oyster abundance has declined Ͼ90% in the past century.…”
Section: Resultsmentioning
confidence: 99%
“…The impacts of introduced pathogens seem to have resulted in significant, widespread, and complex changes throughout the bay. The two protistan pathogens Haplosporidium nelsoni and Perkinsus marinus, classified respectively as a probable and a possible introduction, have been a significant factor in the decline in abundance of the oyster Crassostrea virginica (e.g., Andrews 1979;Kennedy 1996;see Lauckner 1983;Sindermann 1990). In Chesapeake Bay, oyster abundance has declined Ͼ90% in the past century.…”
Section: Resultsmentioning
confidence: 99%
“…The protozoan parasite Perkinsus marinus significantly reduces growth rate, condition index and gametogenesis of its host, Crassostrea virginica (Kennedy et al, 1995;Paytner, 1996;Dittman et al, 2001). A similar pattern has also been shown for Perkinsus olseni in the clam Tapes decussatus (see review in Villalba et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of food intake (entry of energy into the organism) is one of the most important components of the energy balance, and in this case, its reduction led to a reduction in the proportion of energy available for growth in juveniles by 49% in the most infected individuals, even though the energy losses via metabolism were lower in the latter group. Several studies in marine mollusks have found that infectious diseases can alter the energy balance of the host (Newell, 1985;Barber et al, 1988;Kismohandaka et al, 1993;Kennedy et al, 1995;Villalba et al, 2004;Rosenblum et al, 2005;Flye-Sainte-Marie et al, 2007). The magnitude of these changes and their effects depend on the virulence of the parasite, the extent of disease development, and the resistance of the host.…”
Section: Discussionmentioning
confidence: 95%
“…These indicators are highly sensitive and allow anticipation of effects on growth, reproduction, and survival. Several studies have reported that the presence of parasites and/or pathogens in marine mollusks alters their energy balance, leading to a diminution or loss of the animal's capacity for growth or reproduction (Barber et al, 1988;Newell, 1985;Kennedy et al, 1995;Flye-Sainte-Marie et al, 2007). While the marked changes provoked by WS may indicate that associated physiological alterations occur in infected organisms, the dynamics of this response during the evolution of infection are not currently understood, especially during its initial phases in which clinical signs are not evident.…”
Section: Introductionmentioning
confidence: 96%